Uma avaliação do Programa Ciência sem Fronteiras : efeitos sobre desempenho, trancamento e conclusão - Conceição, Otavio Canozzi (2017)
The present dissertation evaluates the Science without Borders program focusing on three outcome variables. To achieve this goal, the work is divided into two essays. The first essay addresses the causal impact of the program on the performance of CsF alumni from the 2013 National Student Performance Exam (ENADE) microdata. The results are compared with two control groups: the first composed by students who also made international academic mobility, but through other initiatives and the second by the non-exchange students. The strategy of comparing the CsF‟s alumni with the exchange students aims to mitigate the problems of self-selection, because we can expect more similar characteristics between these groups, both with regard to motivation to study abroad and observable characteristics. The methodology used was the Propensity Score Matching (PSM), using different pairing algorithms to check the validity of the findings. The results show that the alumni of the program present better grades than the exchange students, both in the general formation part and in the specific component of the ENADE exam. The second essay examines dropout and completion rates in the CsF students‟ course from the microdata of the Higher Education Census of 2014 and 2015. For this purpose, a panel of students was constructed, divided into the same groups of the first essay, which allowed to identify their trajectories in the course. The methodology used involved two techniques: a multinomial logit and the Markov transition matrices. The evidence found shows that CsF students evades more the course and conclude it at lower rates in the expected time, according to the serial grade of the course, than both comparison groups. The results of the multinomial logit model, controlling characteristics of individuals, institutions, courses and regions, suggest that the program has a ceteris paribus effect on the extension of student time in the university.